IMPLEMENTATION OF EXTRACURRICULAR WORK ON ENVIRONMENTAL PROTECTION IN KYRGYZSTAN AT SCHOOL - Asanbekova Ch. A.; Asanbekova A. A. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The article provides the basic concepts of environmental education, which is the main assistant in the implementation of extracurricular activities of schoolchildren on nature conservation. The teacher's activities are aimed at the formation and education of the personality of the student who studies with interest, is able to organize his life, determine the long-term and short-term prospects, find and attract the necessary resources, outline an action plan and assess whether it was possible to achieve the goal. Environmental training and education at school, which is based on optimizing the process of assimilation of the basics of environmental culture by schoolchildren. Environmental education is part of moral education when using the technology of developing environmental culture and extracurricular activities permeated with environmental issues. The main elements and aspects in the implementation of extracurricular activities on ecology at school, an analysis of the state of activities aimed at its development are given. Problems and ways to solve them, gaining knowledge about the world around us, the world of nature and the value attitude towards it, have an educational impact on students and a significant part of extracurricular activities.